Salmonella typhimurium sepsis in a neonate: a rare and challenging case - Dabre, Larissa R.; Sheikh, Samir; Barot, Vaibhavi S.; Amrutiya, Dhruvi; Barot, Shailesh (International Journal of Contemporary Pediatrics, 2025)
Neonatal sepsis attributed to Salmonella infection is a relatively rare phenomenon. It can have varied presentation encompassing mild, subclinical presentations to severe life-threatening complications and death. Prompt administration of appropriate antibiotics forms cornerstone of treatment. Authors present a case of 25-day-old neonate, who presented with fever, lethargy, respiratory distress, and signs of dehydration. Upon evaluation, the neonate was diagnosed with sepsis caused by Salmonella enterica serovar typhimurium. Prompt medical management was initiated, and the neonate responded well to treatment. The patient made a full recovery without any residual comorbidities or complications.